Genetic diversity and ecogeographical differentiation among ribosomal DNA alleles in wild and cultivated barley. - Saghai Maroof, M A (1990)
DNA from 267 accessions of wild barley from ecologically diverse habitats in Israel and Iran and from 92 accessions of cultivated barley from throughout the world were assayed for the 20 ribosomal DNA (rDNA) spacer-length variants that have been identified in the barley species. These 20 spacer-length variants, which are detectable by Southern blot hybridization, serve as markers of rDNA alleles of two Mendelian loci, Rrn1 and Rrn2. All of the populations of wild barley studied were polymorphic for both loci. In wild barley allele 112 (Rrn1) and allele 107 (Rrn2) behaved as widely adapted wild-type alleles; in our sample of cultivated barley allele 112 also behaved as a wild-type allele but allele 104 was somewhat more frequent than allele 107 in Rrn2. A few other alleles were locally frequent in wild barley. However, most of the 20 alleles were infrequent or rare and such alleles were often associated as "hitchhikers" with one of the wild-type alleles in compound two-component alleles. Allelic and genotypic frequencies differed widely in different habitats in correlation with eight of nine factors of the physical environment. Discrete log-linear multivariate analyses revealed statistically significant associations among alleles of Rrn1 and Rrn2. It was concluded that natural selection acting differentially on various rDNA alleles plays a major role in the development and maintenance of observed patterns of molecular and genetic organization of rDNA variability.